Towards achieving circularity in residential building materials: Potential stock, locks and opportunities. (25th January 2021) - Tazi, Nacef; Idir, Rachida; Ben Fraj, Amor
Abstract: The 21 s t century globalization and growth are being accompanied by a tremendous use of residential building materials and has increased the demand for aggregates in concrete-based materials. In the context of France, natural aggregate quarries are dispatched throughout the various regions and generally seem to satisfy the need for aggregates in residential construction. Such however is not the case in those fast growing cities/regions with few natural aggregate quarries. As a follow-up to the waste framework directive 2008/98/EC urging better resource use, this paper explores the ability to achieve circularity practices in residential building materials in French regions. To do so, the framework proposed in this paper aims to close the loop of residential building materials in France and reduce its natural aggregates' consumption. Stock and flows of materials consumed, construction and demolition wastes generated and recycled materials from this sector were assessed through a regional-level material flow analysis. Based on our results, an average reduction in regional natural aggregate extraction of 20 % is obtained when using stock and flows of recycled aggregates stemming from the residential component of construction and demolition wastes and re-injected in new dwellings. The residential wastes employed to reduce natural resource extraction include: concrete, block concrete, stone, solid and hollow bricks from baked clay, tiles, mortar, mineral plaster, glass, sand, and asphalt. The findings of this study also present an overview of the locks and opportunities to achieving the sustainable use of residential building materials. Graphical abstract: Image 1 Highlights: Guidelines for circular economy in French residential sector are provided. Framework approach for identifying the potential stock of residential building materials is provided. Main locks and opportunities to unleash the implementation of circular economy in French residential sector are presented.